The geometric lorenz attractor is a homoclinic class (2004)
An attractor is a transitive set to which all nearby positiveorbits converge. An example of an attractor is the geometric Lorenz attractor [GH]. In this paper we prove that the geometric Lorenz attractor is a homoclinic class.